Motherhood in the Work of Marie NDiaye: Modernising the Madonna and Medea - Eaton, Pauline (Literatūra, 2025)
Two outstanding exemplars of motherhood exist in Western literature: Medea, the epitome of the bad mother in that she murders her two sons as an act of revenge for her betrayal by her husband, and Virgin Mary, idealised not just as a good mother, but as a model of perfection in motherhood. Both Medea and the Madonna have been the subject of reinterpretation over the centuries, a process that continues today. The contemporary French novelist Marie NDiaye has referenced these two iconic figures in the three novels discussed in this essay: La femme changée en bûche (1989), Rosie Carpe (2001) and La vengeance m’appartient (2021). This paper builds on previous analyses of the first two novels by exploring the portrayal of the mother, Marlyne, who features in La Vengeance m’appartient. In this novel the archetypal figure of Medea makes an active re-appearance, twenty years after her presence first emerged into NDiaye’s novelistic universe, and the reader is invited to consider the motivation of a mother who murders her three children and to ask where the blame for this act, to which the mother freely confesses, should lie. The aim of this paper is not to give an answer to that question (which would be contrary to the spirit of the novel) but to posit lines of interpretation which probe the literary representation of the mother.